CHASING GRAVITATIONAL WAVES - Чесноков, Єгор; Чурсанова, Марина; Лінчевський, Ігор (SWorldJournal, 2026)
This paper presents a review of the latest experimental methods for observing gravitational waves, an analysis of the progress achieved to date, as well as a discussion of the most promising technologies and future directions in the field. The twenty-firs